Telescope - telehealth services code of practice for Europe - Rudel, Drago (Informatica Medica Slovenica, 2012)
We present the European project TeleSCoPE - Telehealth Services Code of Practice for Europe. It is developing a comprehensive Code of Practice that relates to those aspects of telemedicine and telecare that are delivered in peoplećs homes and mediated through ICT. This is a 3-year project (2010-2013) co-financed by the European Executive Agency for Health and Consumers. Among 13 project partners from 7 countries, two are from Slovenia. The main output of the TeleSCoPE project will be the Code itself and associated plans to facilitate its adoption by the EU member states. Among its side products is the glossary of terms in telehealth, which was used as a key document when preparing a foundation document for a national strategy on telehealth in Slovenia.
Keywords: Europe; Evropa; Health Services; Kakovost zdravstvenega varstva; Nacionalni, zdravstveni programi; National Health Programs; Organization And Administration; Quality Of Health Care; Telemedicina; Telemedicine; Zdravstvene službe